Weed shoot morphology effects on competitiveness for light in direct-seeded rice - Caton, B.P.; Mortimer, A.M.; Foin, T.C.; Hill, J.E.; Gibson, K.D.; Fischer, A.J. (Wiley, 2001)
The effects of weed shoot morphology on competitiveness for light in rice (Oryza sativa L.) have not been well described quantitatively and are difficult to study empirically. A rice:weed model was used to analyse the effects of weed leaf area densities (LAD; m2 m–3), leaf angles (as leaf light extinction coefficients, kleaf) and maximum heights (Hm, m) on growth and competition with rice. Weed morphologies were hypothetical but empirically based, as follows: LADs were skewed to the bottom or conical, kleaf values varied from 0.2 (erectophile) to 0.8 (planophile), and Hm values were 0.5HR, 1HR and 1.25HR, where HR was rice maximum height. Other parameters were equal to those of rice. Growth and competitiveness were evaluated using mature seed dry weights (g m–2). Short weeds and weeds with conical LADs were weakly competitive, regardless of other traits. For other weed types, interference with rice was positively related to Hm, LAD skewness and more planophile leaves. All three traits were critical determinants of weed interference but no single morphological trait guaranteed competitiveness. All else being equal, weeds with highly skewed LADs produced the most seed dry weight. Planophile leaves were particularly beneficial for short weeds, giving over five times more seed dry weight than erectophile leaves.